Unravelling the antitumor mechanism of Ocoxin through cancer cell genomics - Hernandez-Unzueta, Iera; Telleria-Gonzalez, Uxue; Aransay, Ana María; Martin Rodriguez, José Ezequiel; Sanz, Eduardo; Márquez, Joana (Frontiers in Pharmacology, 2025)
Cancer is one of the leading causes of death worldwide. Many therapies are being used to treat this disease, however, new treatments are now being implemented, since they are not always effective and their secondary effects represent one of the main reasons for cancer patients’ loss of life quality during the progression of the disease. In this scenario, Ocoxin is a mixture of plant extracts, amino acids, vitamins and minerals, known for its antioxidant, anti-inflammatory and immunoregulatory properties, which has shown to exert antitumor effects in many cancers. The aim of this study is to elucidate the mechanism of action of the compound in colorectal cancer, triple negative breast cancer, pancreatic cancer and prostate cancer. Analyses performed through RNA sequencing revealed that the main effect of Ocoxin appears to be the alteration of cell metabolism, especially inducing the process of ferroptosis. Nevertheless, the modulation of the cell cycle was also remarkable. Ocoxin altered 13 genes in common in all the four cancers that were not only associated to metabolism and cell cycle but were also involved in the integrated stress response and unfolded protein response, suggesting that the compound causes the induction of cell death through several pathways. Although the mechanisms vary according to the type of cancer, this study highlights the potential of Ocoxin as an adjunctive treatment to improve outcomes in cancer therapy.